Evaluation of Neonatal Hemolytic Jaundice: Clinical and Laboratory Parameters - Cherepnalkovski, Anet Papazovska; Krzelj, Vjekoslav; Beti Zafirova Ivanovska; Gruev, Todor; Markic, Josko; Aluloska, Natasa; Nikolina Zdraveska; Piperkovska, Katica (ID Design 2012/DOOEL Skopje, 2015)
Neonatal jaundice that occurs in ABO or Rhesus issoimunisation has been recognized as one of the major risk factors for development of severe hyperbilirubinemia and bilirubin neurotoxicity.